Sensory and Statistical Analysis of Banjarbaru Rice Production: Hedonic Evaluation, Sensory Attributes, and Normal Distribution - Mahyudi, Fitri; Surti, Surti; Husinsyah, Husinsyah (Universitas Pendidikan Mandalika, 2025)
This study aims to evaluate the sensory quality and consumer acceptability of Banjarbaru-produced rice, including fortified (Fortivit), biofortified (Nutri Zinc), and conventional (Inpari 32) varieties, through hedonic testing and sensory attribute analysis. The research was conducted in Banjarbaru City, South Kalimantan, covering five sub-districts. A total of 25 respondents participated in sensory assessments evaluating color, aroma, taste, texture, and shape on a 4-point Likert scale. In addition to sensory analysis, the study investigated zinc retention during typical household preparation practices, including repeated washing and standard cooking procedures. Micronutrient content was analyzed using standard laboratory methods, while sensory data were statistically tested using one-way ANOVA. Results showed that Fortivit rice exhibited the highest consumer preference across most sensory attributes, particularly in texture (mean score 3.60) and color (3.44), and demonstrated superior zinc retention (86.2%) compared to Nutri Zinc (69.8%) and Inpari 32 (74.3%). Statistically significant differences were observed in the attributes of color, texture, and shape (p < 0.05), confirming Fortivit’s sensory advantage. Nutri Zinc, while nutritionally valuable, received lower scores and suffered higher micronutrient losses during washing and cooking. The findings highlight the dual importance of both nutritional resilience and sensory appeal in increasing consumer acceptance of fortified rice. Fortivit’s extrusion-based fortification technology offers an effective strategy for micronutrient delivery, particularly in stunting-prevalent regions like South Kalimantan. This study supports the promotion of fortified rice as a feasible public health intervention and emphasizes the need for continued innovation and region-specific consumer education to ensure adoption success.